Characterization and clustering of agronomic characters of several soybean genotypes - M. MUCHLISH ADIE; AYDA KRISNAWATI (Smujo International, 2017)
Adie MM, Krisnawati A. 2016. Characterization and clustering of agronomic characters of several soybean genotypes. Nusantara Bioscience 9: 237-242. The development of improved soybean variety in Indonesia is mostly derived from crossing (51.19%), which requires the availability of gene source to serve as the parental stock. Characterization of 150 soybean genotypes was conducted in Probolinggo, Indonesia, from February to May 2016. The research was arranged in a randomized block design with two replicates. Clustering of agronomic characters was carried out using cluster analysis. The grouping was based on plant age characters (vegetative phase duration, generative phase duration, generative and vegetative ratio, days to maturity), growth characters (plant height, number of filled pods, number of empty pods, number of branches, number of nodes), and seed characters (100-seed weight and seed yield plant-1), which resulted in 10 groups/clusters. Cluster I, II and III consisted of 47, 80, and 13 genotypes, respectively; whereas other clusters consisted of one up three genotypes, respectively. Each cluster represents specific characters. Cluster IV that consisted of three genotypes showed a late maturity (83.5-88.5 days), high number of pods (81.8-83.3 pods plant-1) and high yield plant-1 (21.76- 25.78 g plant-1), but have small seed size (12.24-13.75 g 100 seed-1). Cluster VI consisted of one genotype, and characterized by large seed size (16.79 g 100 seed-1) and high yield plant-1 (15.76 g). Cluster IX (1 genotype) was characterized by early maturity (73 days), unbranched, but produced relatively low yield. The preference of soybean consumer in Indonesia is high yield, in addition to early maturity (< 80 days), and large seed size (>14 g 100 seed-1). Soybean genotypes within cluster IV, VI, and IX are valuable as gene source in the development of superior soybean varieties in Indonesia.